Orang Indo di Belanda: Identitas Campuran dan Pengelolaan Keragaman - Selly Riawanti (Universitas Padjadjaran, 2020)
This paper discusses the relationship between ethnic identity and diversity management by the state, based on the case of the Indo people in the Netherlands. As descendants of mixed-marriage between persons from different ethnic groups who were also unequals in Netherland-Indies colonial society, their citizenship status changes from the colonial period to the decolonization period in the Indies, and eventually in the post-colonial Netherlands. The data is obtained from a qualitative research that consists of literature study and interviews with Indo people and an Indo organization in The Netherlands. Indo identity and culture contain ‘foreignness’ and ‘nativeness’, which could bring advantages or disadvantages, or even threaten their very existence, in different contexts of diversity management by the state. The study found different practices of indoness between three Indo generations in the Netherlands. Intergenerational Indo experiences has constructed a relatively open disposition among the younger generation on their identity and tolerance towards others in the increasingly multicultural Netherlands.